DIAGNOSTICS AND TREATMENT OF BOERHAAVE’S SYNDROME - Yu. V. Chikinev; Ye. A. Drobyazgin; A. S. Polyakevich; I. V. Peshkova (Вестник хирургии имени И.И. Грекова)
The article presents the results of diagnostics and treatment of 12 patients with Boerhaave’s syndrome (men - 9, women - 3). The age of the patients was 19- 68 years old. The prescription of spontaneous rupture of the oesophagus was 7 h- 2 days from moment of the rupture to hospital admission. General aspects of disease were noted in 10 patients, though only 5 patients were directed to the hospital with suspicion on Boerhaave’s syndrome. Emergency surgeries were performed on all patients. At first the opening was carried out, than drainage of posterior lower mediastinum were performed by Savinykh-Rozanov method with wound closure of the oesophagus walls. The complications were noted in 2 patients (the first case-pleural empyema, the second case-pulmonary embolism). Late complications, such as esophagostenosis in the place of wound closure were followed up in 3 patients in terms more than one month after operation.